Vaccine cold chain management practices in primary health centers providing an expanded immunization program in Northwest Ethiopia: self-reported and actual practice observational study - Ergetie, Firdawek Shenkute; Kassaw, Abebe Tarekegn; Sendekie, Ashenafi Kibret (Frontiers in Public Health, 2023)
Background: Vaccines are vital health commodities that need an appropriate supply chain system.They could be transported, stored, and used at appropriate temperatures. The purpose of this study was to assess vaccine cold chain management practices in primary health centers offering an expanded program of immunization (EPI) in Bahir Dar, Northwest Ethiopia.Methods: A self-reported and actual practice observational cross-sectional study was conducted at primary public health centers in the Bahir Dar city administration from August 15 to 30, 2021.A simple random sampling method was used to select study participants. An interviewadministered questionnaire and direct actual practice observation were used to collect data. The data was entered into the Epi-data 4.6 program and analyzed using SPSS version 25. Participants' knowledge, storage and transport conditions, IPLS management, and vaccine cold chain management practices were examined using independent samples t-tests and one-way ANOVA tests.Findings: A total of 50 respondents from ten health centers were enrolled in the study. Most of the EPI service providers had good knowledge (60%) and good practice in vaccine storage and transport (74%). However, more than two-thirds (68%) of EPI service providers had poor integrated pharmaceutical logistics system (IPLS) management. Only half (50%) of the health centers had good actual vaccine cold chain management practices. Higher educational background, longer work experience, and receiving training and supervision in EPI services, IPLS management, and vaccine inventory management resulted in higher knowledge, storage and transport management, IPLS management, and vaccine cold chain management practices.Although most EPI service providers in an interview assessment reported having good knowledge and good vaccine storage and transport management, only half of the health facilities followed the standard. Stakeholders are recommended to play a vital role in improving practices related to EPI services.